Design of diblock co-oligomers as low bandgap small molecules for organic solar cells - Oliveira, Eliezer Fernando [UNESP]; Lavarda, Francisco Carlos [UNESP] (Taylor & Francis, 2017)
The properties of a particular kind of small molecule that is built from two oligomers of different monomers, i.e. a diblock co-oligomer, as the electron donor in the active layer of organic solar cells are investigated theoretically. For these molecules, this work shows that it is possible to predict the energies of the frontier molecular orbitals by knowing the same energies for the oligomers that constitute the diblock, opening the possibility of designing new materials with optimal energy levels and optical properties. Furthermore, it was observed that the optical absorption bands of these diblock co-oligomers were broader than that of the constituent oligomers and also of the homopolymers, allowing greater absorption of photons and possibly an improved electric current in the device. It was also shown that these phenomena are size-dependent.
Keywords: Computational modelling; DFT; diblock co-oligomers; optical properties; organic solar cells